2000
DOI: 10.1080/10473289.2000.10464029
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of PM10 Samplers under Calm Air Conditions

Abstract: The size range of airborne particles that is closely related to specific deposition regions in the human respiratory tract and excess lung burden of these deposited particles is associated with disease. Size-selective sampling, therefore, needs to be performed to assess the related health risks. Performance criteria applied to these samplers must be well characterized in order to provide accurate and reliable results. The PM 10 samplers that have been used in place of the total suspended particulate samplers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…A metallic well without oil, however, produced a broad separation curve with a 50% cut-off diameter larger than the design value of 2.5 µm. Lai and Chen (2000) also compared aerosol separation efficiency of inlet heads of a Harvard impactor, Personal Environmental Monitor (PEM) and Anderson dichotomous sampler (model 241). Their study showed that particle bounce-off effect was minimized by a silicone oil coating on the impaction plate.…”
Section: Introductionmentioning
confidence: 99%
“…A metallic well without oil, however, produced a broad separation curve with a 50% cut-off diameter larger than the design value of 2.5 µm. Lai and Chen (2000) also compared aerosol separation efficiency of inlet heads of a Harvard impactor, Personal Environmental Monitor (PEM) and Anderson dichotomous sampler (model 241). Their study showed that particle bounce-off effect was minimized by a silicone oil coating on the impaction plate.…”
Section: Introductionmentioning
confidence: 99%
“…As the ideal samplers do not really exist, the performance characteristics of size-selective samplers are usually computed numerically, using experimental data from measurements of the sampling efficiency as a function of particle aerodynamic diameter (Kenny and Bartley 1995). Many studies have applied a statistical approach to measure the sampler bias and imprecision as a function of particle aerodynamic diameter, and have combined these items into an overall measurement of sampler performance, termed inaccuracy (Bartley and Breuer 1982;Bowman et al 1984; Bartley and Doemeny 1986;Kenny and Liden 1989;Kenny and Bartley 1995) or Mean Square Error (MSE) (Chen et al 1999;Lai and Chen 2000). In addition to modeling the possible collected mass bias of the candidate sampler as compared to the ideal sampler, these statistical approaches also calculate variations between and within specimens of the same sampler type.…”
Section: Introductionmentioning
confidence: 99%
“…Although both methods (polygonal approximation and curve-fitting) can be applied to the same data, the estimates obtained using both methods were quite similar, and so this study ignores possible variations in the total number of challenge aerosols. Currently, PM10 sampler performance using polydisperse aerosols and particle aerodynamic diameters that approach 50 µm, under calm air conditions can be evaluated in the laboratory (Lai and Chen 2000). More precise separation curves, appropriate aerosol size spread, and convenient statistical methods, including mass and number bias or imprecision, are considered in evaluating sampler performance.…”
Section: Introductionmentioning
confidence: 99%
“…Of this total flow, 15 l/min was diverted into the "fine" ( 2.5 µm) stream while 1.67 l/min went straight down the "coarse" ( 2.5 µm) stream. Particles were collected on glass fiber filters for later analysis (Lai and Chen, 2000). Information on the instrument can be found in the Sierra Andersen instruction manual (Environmental Monitoring Systems, Laboratory, 1985).…”
Section: The Dichotomous Samplermentioning
confidence: 99%
“…tube" that goes straight down the "coarse" ( 2.5 µm) stream. The two divergent size segregated particle trains are subsequently collected on separate glass fiber filters for later analysis (Lai and Chen, 2000).…”
Section: The Dichotomous Samplermentioning
confidence: 99%